Rigor Mortis and Its Management in Dental Autopsy Procedures - Rizki Tanjung; Intan Farizka; Siti Salsabila Kirana; Agnes Elizabeth Yuwono; Ailsa Fadhilah Putridwita; Aldrina Wulan Eka Suci; Elsa Christy (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Forensic Odontology plays a crucial role in forensic investigations, including determining the postmortem interval (PMI). Rigor mortis is one of the early signs of death, often presenting challenges during oral examinations. Dental autopsy is a procedure that can address these challenges, enabling a thorough examination of the teeth even in the presence of rigor mortis. Review: Rigor mortis represents a major obstacle in dental autopsy procedures. Muscle stiffness hampers mouth opening and access to the oral cavity. Various techniques can be employed to perform dental autopsies in cases of rigor mortis, such as the use of mouth gags, trismus screws, and myotomy. Jaw resection techniques may also be employed to provide better access to dental structures. Conclusion: Rigor mortis significantly limits oral cavity access during dental autopsy procedures. Characterized by muscle stiffness, presenting a challenge during dental autopsy examination of the oral cavity.